Administrative practice and rational inquiry in postmodern public administration theory - Zwart, Frank de (2002)
This article explores postmodern reasoning in academic public administration. It argues that the antiscience and proliberation arguments that abound in postmodern writing in public administration are informed by a fallacy: conflating administrative practice and the scientific study of that practice. In effect, postmodernists confuse wrongs of bureaucracy with arguments against modern science and then propagate relativism to clear up the muddle they created. This article opposes that package deal. It argues that the main objection postmodern authors have against science and administration - neglect of the variety of subjects' points of view - has nothing to do with positivism or modern science and cannot be cured with relativism. - Reproduced.
Keywords: Public administration